UPAYA PENINGKATAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN DI KELAS XI SMAN 2 BALIGE - Rismauli Berutu (Universitas Negeri Medan, 2019)
This research was conducted in Class XI SMA Negeri 2 Balige. The goal is to take learning material on the Christian attitude in the development of science. The subject of this research was 28 students in Class XISMA Negeri 2 Balige. Student learning outcomes data were captured by pretest and post test. The results of the study concluded that using the jigsaw method can improve student learning motivation. Increasing student learning motivation in the pre-cycle is 50%,% (14 students) to 71.4% (20 students) in Cycle II, to 85.71% (25 students). According to the data above, it can be interpreted that learning motivation has been dominated by some 96.42% of students. Thus, looking at learning outcomes at the initial observation, there appears to be a significant percentage increase in completeness of student learning outcomes from 50% (14 students) to 71.4 % (20 students) in Cycle II, became 85.71% (25 students), becoming 96.42% (27 students). Based on the results of the study above the jigsaw method can increase student learning motivation, reduce students' boredom and saturation in learning and make students more active in learning. Keywords: Learning Motivation, Christianity